Digital Based Learning Media Development to Increase Baseball Technique for Grade VI Elementary School Students - Pratama, Diyan Surya; Sumarni, Sri; Safaruddin, Safaruddin; Iyakrus, Iyakrus (Journal of Research and Educational Research Evaluation, 2021)
This study aims to produce digital based learning media to improve the Baseball games technique in grade VI Elementary School Students in Palembang city with a total of 40 students by using a limited trial (small group) to 10 students and a vast trial (large group) by using 30 students. Analysing technique in this research is a linear regression model. The results in this study indicate that the implementation of digital media based learning process with Baseball basic technique is used in elementary school. In stage of field test, based on 3 test which examined to the students, that is ball throwing, ball hitting and winning techniques. At the Pre-Test score of 55, 58 and 60 (Quite Good) and in Post-Test getting score of 72, 75 and 79, the criteria increased to Good. The average score of Post-Test is 9.06 with 1.89 as the deviation standard, but on Pre-Test have 1.89 it shows that the assesement on Post-test group is varied more. It can be concluded that digital based learning of media to improve Baseball game technique in grade VI Elementary School Students are valid, practical and feasible to use.